2020
DOI: 10.1590/0004-282x20190159
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in chronic migraine: a cross-sectional study in a clinic-based sample

Abstract: Cognitive impairment has been described in all phases of a migraine attack and interictally. However, the prevalence and phenotype of such impairment in chronic migraine (CM) have not yet been studied. Objectives: The aim of this study was to evaluate both the prevalence of the objective cognitive deficit in patients with CM and the factors underlying its etiology. Methods: 144 patients with CM and 44 age-matched patients with low-frequency episodic migraine (EM) (a maximum of 4 headache days per month) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 33 publications
3
29
1
Order By: Relevance
“…It was found that the severity of memory decline is related to migraine frequency and duration [ 16 ]. A similar hypothesis was seen in several other articles [ 17 - 19 ]. Some studies found a discordant result of the migraine and dementia link [ 20 - 21 ].…”
Section: Reviewsupporting
confidence: 90%
“…It was found that the severity of memory decline is related to migraine frequency and duration [ 16 ]. A similar hypothesis was seen in several other articles [ 17 - 19 ]. Some studies found a discordant result of the migraine and dementia link [ 20 - 21 ].…”
Section: Reviewsupporting
confidence: 90%
“…From the 15,316 records identified by the search methods, 37 studies (Demirci and Savas, 2002 ; Weiner et al, 2006 ; Meeks et al, 2008 ; Shega et al, 2010 , 2012 ; Jonsson et al, 2011 ; Walteros et al, 2011 ; Ko et al, 2013 ; Pirrotta et al, 2013 ; Butterworth et al, 2014 ; Docking et al, 2014 ; Hagen et al, 2014 ; Martinsen et al, 2014 ; Pickering et al, 2014 ; Coppieters et al, 2015 ; Meeus et al, 2015 ; Öncü et al, 2015 ; Dos Santos Ferreira et al, 2016 ; Fernández-Lao et al, 2016 ; Santangelo et al, 2016 ; Schepker et al, 2016 ; Kaiho et al, 2017 ; Tzeng et al, 2017 ; Whitlock et al, 2017 ; Jordan et al, 2018 ; Ojeda et al, 2018 ; Pidal-Miranda et al, 2018 ; Qu et al, 2018 ; Van Der Leeuw et al, 2018b , 2020 ; Veronese et al, 2018 ; Gu et al, 2019 ; Ikram et al, 2019 ; Samartin-Veiga et al, 2019 ; Kotb et al, 2020 ; Latysheva et al, 2020 ; Nakai et al, 2020 ) were identified, a total of 52,373 patients with CP and 80,434 healthy control participants. These 37 studies included different types of CP: headache ( n = 7); fibromyalgia syndrome (FM) ( n = 6); low back pain ( n = 3); whiplash-associated disorder ( n = 2); foot pain ( n = 2); cancer pain ( n = 1); low back pain and knee pain ( n = 1); neuropathic pain ( n = 1); musculoskeletal pain, neuropathic pain, and FM ( n = 1); post-herpetic neuralgia ( n = 1); non-cancer pain ( n = 1); and other unclassified CP ( n = 13).…”
Section: Resultsmentioning
confidence: 99%
“…migraine chronification or medication overuse. Compared with episodic migraine, individuals with chronic migraine are observed to have more cognitive impairment [41]. Furthermore, a review found that individuals with complicated medication overuse headache (MOH) have better outcomes after inpatient treatment indicating that cases of MOH may be inclined to seek hospital treatment [42].…”
Section: Strengths and Limitationsmentioning
confidence: 99%